Prevalence of Salmonella in marketed Penaeus monodon shrimps in North Western Province, Sri Lanka - J. Kamalika H. Ubeyratne (2018)
The examination of a total of 180 samples from both captured and cultured shrimps from Sri Lanka for the presence of Salmonella revealed an overall prevalence of 12.8%. The prevalence of Salmonella in captured shrimps and cultured shrimps was 14.4% and 11.1% respectively, but the difference was not statistically significant (p = 0.66). The serovar most frequently isolated was S. Newport (47.8% of the isolates), followed by S. Weltevreden (8.7%). © 2008 Schlütersche Verlagsgesellschaft mbH & Co. KG.